ENHANCING EARLY CHILHOOD’S ENGLISH VOCABULARY AT TK ‘AISYIYAH BUSTANUL ATHFAL MERDUATI BANDA ACEH THROUGH DUOLINGO ABC APPLICATION - Rina Sulicha (Linguistik : Jurnal Bahasa dan Sastra, 2026)
This study investigates the effectiveness of the Duolingo ABC application in enhancing English vocabulary acquisition among young learners at TK 'Aisyiyah Bustanul Athfal Merduati Banda Aceh, Indonesia. Employing a true experimental design with pre-test and post-test control group framework, the study involved 32 kindergarten students divided into two groups: an experimental class (B-1, n=16) and a control class (B-2, n=16). The experimental group received vocabulary instruction using the Duolingo ABC application as a digital instructional medium, while the control group was taught through conventional visual aids, namely puppets and picture cards. The teaching materials covered two main themes: Basic Vocabulary (alphabet, names of fruits, and names of animals) and Basic Sentences (nominal and verbal sentences), conducted over ten meetings. Data were analyzed using descriptive statistics and a paired-sample t-test via SPSS. The results revealed that the experimental group achieved a notably higher mean post-test score (M = 96.88, SD = 4.79) compared to the control group (M = 78.75, SD = 7.19), with a statistically significant difference (Sig. 2-tailed = 0.000, p 0.05). These findings demonstrate that the integration of the Duolingo ABC application as a technology-based instructional tool significantly improved students' English vocabulary mastery and promoted more consistent learning outcomes across learners. This study contributes empirical evidence supporting the adoption of gamified digital learning applications in early childhood English language education.